Aspek Implementasi Wireless Sensor Network Pada Taman Nasional Tesso Nilo - Indah Kurniati; Indra Yasri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Forest fires in Indonesia every year always happen that a national disaster. To overcome this problem have wireless sensor network as a solution. But the sensor node has limited ability in terms of memory capacity, bandwidth and energy. Among the issues, energy consumption is a concern of many researchers because the sensor nodes using the battery as energy. Therefore, in this paper will be the implementation strategy of wireless sensor networks in Tesso Nilo National Park to prevent fires. The results obtained by the network topology and routing protocols are appropriate for the location of Tesso Nilo National Park is a mesh topology and routing protocols directed diffusion.Keywords : Wireless Sensor Networks, Mesh, Directed Diffusion